2014
DOI: 10.1155/2014/635108
|View full text |Cite
|
Sign up to set email alerts
|

Human CD38hiCD138+Plasma Cells Can Be Generated In Vitro from CD40-Activated Switched-Memory B Lymphocytes

Abstract: B lymphocyte differentiation into long-lived plasma cells is the keystone event for the production of long-term protective antibodies. CD40-CD154 and CD27-CD70 interactions are involved in human B lymphocyte differentiation into CD38hiCD138+ cells in vivo as well as in vitro. In this study, we have compared these interactions in their capacity to drive switched-memory B lymphocytes differentiation into CD38hiCD138+ plasma cells. The targeted B lymphocytes were isolated from human peripheral blood, expanded for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Parameters for the antigen–antibody complex formation were obtained from the average values for binding with monoclonal antibodies [ 59 ]. The ranges for time lags t memory and t naive were calculated from known data on lymphocyte physiology [ 60 , 61 ] and experimental results [ 34 ] (see Text S1 for the calculation details).…”
Section: Methodsmentioning
confidence: 99%
“…Parameters for the antigen–antibody complex formation were obtained from the average values for binding with monoclonal antibodies [ 59 ]. The ranges for time lags t memory and t naive were calculated from known data on lymphocyte physiology [ 60 , 61 ] and experimental results [ 34 ] (see Text S1 for the calculation details).…”
Section: Methodsmentioning
confidence: 99%
“…We adopted an in vitro differentiation protocol of human peripheral B-cells to generate human ASCs ( 68 ). Isolated B-cells from healthy donors were stimulated with CpG for 1 day.…”
Section: Resultsmentioning
confidence: 99%
“…Human PCs only represent ∼0.25% of total bone marrow cells and home to different tissues in the human body, making extensive molecular analysis and functional studies challenging ( 5 ). Protocols for in vitro differentiation of human peripheral B-cells into ASCs ( 68 ) form the basis for phenotypic and functional studies ( 9, 10 ). Studies in mice have shown divergent gene expression profiles for the different Ig class PCs ( 11 ) and different expression profiles were observed comparing human class-switched germinal center (GC) B-cells from human tonsils as compared to non-class switched cells ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…B lymphocytes were pushed into differentiation in BPFM using a simple three-step model involving a shift in the L4.5 : B-cell ratio and modifications of cytokines, as previously described [47] (Figure 2(a)). As previously observed, CD38 and CD39 expression rapidly increased following B-cell activation (Figure 2(b), D8).…”
Section: Resultsmentioning
confidence: 99%
“…In our model, the source of B lymphocytes is also peripheral blood, but the selection method we use includes CD27 − IgG- and IgA-positive cells [49] and excludes CD27 + IgD + IgM + cells [64], which are, respectively, absent and present in Jourdan and Cocco culture systems. Our culture model was initiated by an 8-day expansion step generating CD40-activated memory B lymphocytes [47, 65]. The expansion rate we obtained was at least 20-fold; that is, starting with 1 × 10 6 switched memory B lymphocytes on day 0, we could generate up to 20 × 10 6 cells.…”
Section: Discussionmentioning
confidence: 99%